2018
DOI: 10.1103/physrevlett.121.035501
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Debye-Process in Monohydroxy Alcohols: 5-Methyl-2-Hexanol Investigated by Depolarized Light Scattering and Dielectric Spectroscopy

Abstract: The slow Debye-like relaxation in the dielectric spectra of monohydroxy alcohols is a matter of long-standing debate. In the present Letter, we probe reorientational dynamics of 5-methyl-2-hexanol with dielectric spectroscopy and depolarized dynamic light scattering (DDLS) in the supercooled regime. While in a previous study of a primary alcohol no indication of the Debye peak in the DDLS spectra was found, we now for the first time report clear evidence of a Debye contribution in a monoalcohol in DDLS. A quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 23 publications
12
60
0
Order By: Relevance
“…As already stressed before, the TDI measurements detect at each T and q only one relaxation process, and accounts for the total strength of the α and β JG processes. A clear change in the T -dependence of can be observed for all q values around T g = 154 K, as expected when the glass transition occurs, whereas no discontinuity is observed at T αβ = 181 K. This is a well-know result from DS and depolarized dynamic light scattering measurements, that is when the β JG relaxation separates from the structural one no discontinuity in the total strength is detected 34,35 . It is interesting to notice that also at 37 nm −1 , where the β JG relaxation is the dominant relaxation channel, a clear change in the temperature dependence of the contrast is observed at T g , thus highlighting the sensitivity of the β JG relaxation to the glass-transition, as already shown for the dielectric strength of the β JG process at T g 1 .…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…As already stressed before, the TDI measurements detect at each T and q only one relaxation process, and accounts for the total strength of the α and β JG processes. A clear change in the T -dependence of can be observed for all q values around T g = 154 K, as expected when the glass transition occurs, whereas no discontinuity is observed at T αβ = 181 K. This is a well-know result from DS and depolarized dynamic light scattering measurements, that is when the β JG relaxation separates from the structural one no discontinuity in the total strength is detected 34,35 . It is interesting to notice that also at 37 nm −1 , where the β JG relaxation is the dominant relaxation channel, a clear change in the temperature dependence of the contrast is observed at T g , thus highlighting the sensitivity of the β JG relaxation to the glass-transition, as already shown for the dielectric strength of the β JG process at T g 1 .…”
Section: Resultssupporting
confidence: 78%
“…The T -dependence of the β JG -relaxation was instead modeled using the Arrhenius equation: the reduced activation energy found here ( E / k B = 3.3(1) × 10 3 K) agrees with the one reported in ref. 34 . The obtained curves (dash-dotted lines) were then scaled onto the relaxation time data measured by TDI in order to identify unambiguously the α and β JG processes (solid lines in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the interpolation of the PCS-α-process reveals a common spectral shape for 1P and its associated phenyl alcohol isomers. We note that prior studies of the monoalcohols 5-methyl-2-hexanol and 2-ethyl-1-butanol also revealed a very similar α-process shape [15], which indicates a common α-process shape in a broader range of monoalcohols.…”
Section: Discussionsupporting
confidence: 57%